A Critique on the Book “Discourse Evolution of the Report of Karbala Event” with Laklau and Muffes Discourse Approach. - Seyyed Mohammad Rahim Rabbanizadeh; Sayed Hesam Mohammad Zadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This research has utilized a critical method based on Lalau and Muffes discourse approach to scrutinize the book of “Discourse Evolution of the Report of Karbala Event”. The main question of this research is that based on which sort the discourses (emotional, transcendental, and historical) mentioned in this book are set. The conclusion indicates that the Karbala event has not been investigated as a historical and objective event so that it has not been referred to the historical facts of the Karbala event, but the writers’ positions in various discourses have been checked out in the psychological aspect of the event, so the statistical measures in this book cannot be valid. The sign and motto of the discourses under consideration is unclear, and ignores the power ratio in the incident report, and makes no mention of competing discourses in the report of the Karbala event.